2016
DOI: 10.1007/s40843-016-5067-4
|View full text |Cite
|
Sign up to set email alerts
|

N,O-codoped porous carbon nanosheets for capacitors with ultra-high capacitance

Abstract: Significant enhancement of energy density of electrical double layered capacitors is a major challenge for electrochemical capacitors to conquer the emerging field of large scale renewable energy storage. The enhancement of specific capacitance is an effective strategy to obtain higher energy density. Addition of redox mediator in the electrolyte as pseudocapacitive sources could enhance the specific capacitance, but well-coupled electrode materials should be developed as well. Herein, as a proof-of-concept ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…In comparison with batteries, both types of supercapacitors generally offer higher power densities, but lower energy densities. With the rapid development of flexible electronics, various elec-trode materials including carbon materials [7,[19][20][21], metal oxides/hydroxides [22][23][24], conductive polymers [25][26][27] and their associated composites have been developed to fabricate flexible supercapacitors.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison with batteries, both types of supercapacitors generally offer higher power densities, but lower energy densities. With the rapid development of flexible electronics, various elec-trode materials including carbon materials [7,[19][20][21], metal oxides/hydroxides [22][23][24], conductive polymers [25][26][27] and their associated composites have been developed to fabricate flexible supercapacitors.…”
Section: Introductionmentioning
confidence: 99%
“…The element mapping clearly reveals that the nitrogen element is dispersed homogeneously in the SAC‐4 sample. Oxygen–containing groups can provide pseudo‐capacitance, which also contribute to the enhancement of overall capacitive performance …”
Section: Resultsmentioning
confidence: 97%
“…The content of N‐5 and N−X can contribute to the faradaic reaction‐based pseudocapacitance effect, which can enhance the specific capacitance of the sample . It is reported that N−Q exhibit electron donor ability and can facilitate electron transfer to improve the electrical conductivity ,. The electrical conductivity of SAC‐4 is estimated to be 848 S m −1 , which is higher than SAC‐2 (618 S m −1 ), SAC‐6 (485 S m −1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the capacitance retention rate of up to 95.2%. As a result, flexible fibrous supercapacitors have shown great potential in portable and wearable electronic devices, creating new opportunities for sustainable development and self‐development in nanometer equipment in the near future …”
Section: Conclusion and Perspectivementioning
confidence: 99%